Pathogenetic Interplay Between IL-6 and Tryptophan Metabolism in an Experimental Model of Obesity - Mondanelli, Giada; Albini, Elisa; Orecchini, Elena; Pallotta, Maria Teresa; Belladonna, Maria Laura; Ricci, Giovanni; Grohmann, Ursula; Orabona, Ciriana (Frontiers in Immunology, 2021)
Obesity is a metabolic disease characterized by a state of chronic, low-grade inflammation and dominated by pro-inflammatory cytokines such as IL-6. Indoleamine 2,3-dioxygenase 1 (IDO1) is an enzyme that catalyzes the first step in the kynurenine pathway by transforming l-tryptophan (Trp) into l-kynurenine (Kyn), a metabolite endowed with anti-inflammatory and immunoregulatory effects. In dendritic cells, IL-6 induces IDO1 proteasomal degradation and shuts down IDO1-mediated immunosuppressive effects. In tumor cells, IL-6 upregulates IDO1 expression and favors tumor immune escape mechanisms. To investigate the role of IDO1 and its possible relationship with IL-6 in obesity, we induced the disease by feeding mice with a high fat diet (HFD). Mice on a standard diet were used as control. Experimental obesity was associated with high IDO1 expression and Kyn levels in the stromal vascular fraction of visceral white adipose tissue (SVF WAT). IDO1-deficient mice on HFD gained less weight and were less insulin resistant as compared to wild type counterparts. Administration of tocilizumab (TCZ), an IL-6 receptor (IL-6R) antagonist, to mice on HFD significantly reduced weight gain, controlled adipose tissue hypertrophy, increased insulin sensitivity, and induced a better glucose tolerance. TCZ also induced a dramatic inhibition of IDO1 expression and Kyn production in the SVF WAT. Thus our data indicated that the IL-6/IDO1 axis may play a pathogenetic role in a chronic, low-grade inflammation condition, and, perhaps most importantly, IL-6R blockade may be considered a valid option for obesity treatment.